Malformations in Late Devonian brachiopods from the western Junggar, NW China and their potential causes - Zong,Ruiwen; Gong,Yiming (PeerJ, 2022)
Although malformations are found in both extant organisms and the fossil record, they are more rarely reported in the fossil record than in living organisms, and the environmental factors causing the malformations are much more difficult to identify for the fossil record. Two athyrid brachiopod taxa from the Upper Devonian Hongguleleng Formation in western Junggar (Xinjiang, NW China) show distinctive shell malformation. Of 198 Cleiothyridina and 405 Crinisarina specimens, 18 and 39 individuals were malformed, respectively; an abnormality ratio of nearly 10%. Considering the preservation status and buried environment of the abnormal specimens, and analysis of trace elements and rare earth elements from whole-rock and brachiopod shells, we conclude that the appearance of malformed athyrids is likely related to epi/endoparasites, or less likely the slightly higher content of heavy metal in the sea.
Keywords: Malformation; Athyridae; Hongguleleng Formation; Famennian; Xinjiang; NW China